WAYANG CENK BLONK: BALI'S LOCAL GENIUS AS A COMMUNICATION MEDIUM FOR WETLAND MANAGEMENT - Sadwika, I Nyoman; Liska, Luh De; Dewi, Ni Pt. Pande Mirah Surya; Parwati, Ni Putu Yuniarika; Cahayani, Ni Luh Putu (International Conference On Social Science Education, 2025)
One of the challenges in environmental conservation is the lack of innovative and culturally-based approaches capable of reaching diverse segments of society. The aim of this study is to explore the use of wayang kulit as a communication medium to support sustainable wetland management. The research object is the performance of Wayang Cenk Blonk Series 29: Reklamasi Teluk Benoa. The data source comes from the dialogues between wayang characters referencing the reclamation of Teluk Benoa, presented by the dalang (puppeteer) I Wayan Nardayana. Data collection techniques employed include participant observation, documentation, and interview. The findings of this study will be presented descriptively and argumentatively. Data validity is ensured through source and method triangulation. Wayang Cenk Blonk Seri 29 meets the parameters of effective communication in delivering messages related to the reclamation of Teluk Benoa with the categories of clarity, conciseness, completeness, consideration, and concreteness. Reclamation involves actions taken by individuals to improve the value of land resources, considering both environmental and socio-economic factors, through processes such as filling land, draining, or drying it. The mangrove forest ecosystem is highly fragile and vulnerable to damage, which can occur through direct mechanical actions, such as cutting or dismantling, draining, and drying it. Reclaimed land tends to lower the organic matter and nitrogen content of the soil. Reclamation also results in a decrease in the total microorganisms, fungi, and soil respiration.